A Novel GJC2 Mutation Associated with Hypomyelination and Müllerian Agenesis Syndrome: Coincidence or a New Entity? - Yalcinkaya, Cengiz; Erturk, Ozdem; Tuysuz, Beyhan; Yesil, Gozde; Verbeke, Jonathan I.M.L.; Keyser, Britta; Stuhrmann, Manfred; Steinemann, Doris; Sistermans, Erik A.; van der Knaap, Marjo S. (Neuropediatrics, 2012)
In recent years, several new white matter diseases have been identified based on magnetic resonance imaging and clinical findings. For most newly defined disorders the genetic basis has been identified. However, there is still a large group of patients without a specific diagnosis. Hypomyelinating leukodystrophies are the largest group among them. In some disorders characterized by hypomyelination only central nervous system involvement is observed, but in some disorders involvement of other organs is observed as well, such as eyes or teeth. Pelizaeus-Merzbacher-like disease (PMLD) is an autosomal recessive hypomyelinating disorder of the central nervous system characterized by nystagmus, ataxia, and progressive spasticity. The disease is caused by mutations in GJC2, the gene that encodes the gap junction protein connexin 47. Here we describe hypomyelination and Müllerian agenesis syndrome in a girl who is homozygous for a novel mutation in the GJC2 gene. It is an open question whether this is an association by chance or a feature of PMLD not previously noted.
Keywords: hypomyelination; Müllerian agenesis; Pelizaeus-Merzbacher-like disease